2019
DOI: 10.1039/c8nj04236e
|View full text |Cite
|
Sign up to set email alerts
|

Selective chemotherapy and imaging of colorectal and breast cancer cells by a modified MUC-1 aptamer conjugated to a poly(ethylene glycol)-dimethacrylate coated Fe3O4–AuNCs nanocomposite

Abstract: The combination of diagnosis and targeted therapy within a single nanoplatform is one of the remarkable advances in molecular medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…[163] In addition, metal NCs-based nanocomposites, with modified aptamer sequences that are specific to mucin 1, were also used for selective imaging and chemotherapy of human breast cancer cells. [164,165]…”
Section: Aptamer Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[163] In addition, metal NCs-based nanocomposites, with modified aptamer sequences that are specific to mucin 1, were also used for selective imaging and chemotherapy of human breast cancer cells. [164,165]…”
Section: Aptamer Targetingmentioning
confidence: 99%
“…The Au NCs-Fe 3 O 4 @ SiO 2 nanocomposites functionalized with mucin 1 aptamer have been successfully used in the selective detection, imaging, and chemotherapy of colorectal and breast cancer cells. [165] Figure 4. AS1411-aptamer-decorated Au NCs for enhanced radiotherapy.…”
Section: Magnetic Targetingmentioning
confidence: 99%
“…In some instances aptamers can also be used for therapeutics or for combined diagnostics and therapeutics (theranostics). Examples include (1) various aptamers to human immunodeficiency virus (HIV) proteins that either prevent virus entry or replication [7,[25][26][27][28][29], (2) the S-PS 8.4 aptamer that recognizes Salmonella enterica and inhibits invasion of the bacteria into human monocytes [30], (3) two DNA aptamers A9 and B4 against the H9N2 avian influenza virus that inhibit viral infection [31], and (4) a DNA aptamer against MUC-1 that was applied in a nanocomposite for fluorescent imaging and demonstrated to inhibit the proliferation of colorectal (HT-29) and breast (MCF-7) cancer cells [32].…”
Section: Aptamers In Diagnosticsmentioning
confidence: 99%
“…During the last decade, poly(ethylene glycol) dimethacrylate (PEGDMA) and poly(methyl methacrylate) (PMMA) have been exploited a lot as prodrugs, and many matrix structures with biocompatibility and safety have been designed and studied. [4][5][6][7][8] Furthermore, it has been well demonstrated that covalent conjugates of drug molecules associated with these polymers can produce drug agents with excellent effect. 9,10 Emulsion polymerization is the most common method for synthesizing nano/micro-scale polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polymers provide a range of benefits in drug delivery applications, including controlled release of drugs, adjustable pharmacokinetic and biodistribution profile, and improved drug safety. During the last decade, poly(ethylene glycol) dimethacrylate (PEGDMA) and poly(methyl methacrylate) (PMMA) have been exploited a lot as prodrugs, and many matrix structures with biocompatibility and safety have been designed and studied 4–8 . Furthermore, it has been well demonstrated that covalent conjugates of drug molecules associated with these polymers can produce drug agents with excellent effect 9,10 …”
Section: Introductionmentioning
confidence: 99%